Analisis Yuridis terhadap Penerapan Sistem Pembuktian Terbalik Berdasarkan Undang-undang Tindak Pidana Korupsi - Rahmayanti Rahmayanti; Muhammad Arif Maulana; Stanley Alvin; Nadya Elvara Lili Paly (JURNAL MERCATORIA, 2020)
The eradication of corruption was carried out in many ways, one of which with a reverse proof system which was established with the act of eradication of corruption crimes. The upside-down reproof is an aberration of evidence in the act of events. In order not to happen dualism rules in reverse proof it must have a clear criminal law rules in the use of the reversed evidence formulation. From all the explanations about this reverse proof law, as for the reverse-proof law, using the purely reverse-proof law and reason behind the limited changes in the criminal act Corruption, the upside-down proof only in the application of the trial of the judge never to provide the origin of the property but based on the evidence given by the public prosecutor.